2003
DOI: 10.1111/1467-629x.00081
|View full text |Cite
|
Sign up to set email alerts
|

Auditor conservatism and voluntary disclosure: Evidence from the Year 2000 systems issue

Abstract: This study further examines the phenomenon of conservative auditor behaviour by considering the level of voluntary disclosure of Year 2000 remediation information in company annual reports. Previous studies have provided evidence of conservative auditor behaviour by examining the link between Big 6 auditor choice and accruals (Francis and Krishnan 1999;Becker et al. , 1998;Defond and Subramanyam 1998). Protecting their reputation capital increases Big 6 auditor incentives to act conservatively to avoid litigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 9 publications
2
36
0
Order By: Relevance
“…Several theoretical and empirical studies examined this issue such as the studies of Jensen (1983); Healy and Palepu (2001); Ho and Wong (2001), Bujaki and McConomy (2002), Clarkson et al, (2003), Barako et al (2006) and Cheung (2010).…”
Section: Board Of Directors's Characteristicsmentioning
confidence: 99%
“…Several theoretical and empirical studies examined this issue such as the studies of Jensen (1983); Healy and Palepu (2001); Ho and Wong (2001), Bujaki and McConomy (2002), Clarkson et al, (2003), Barako et al (2006) and Cheung (2010).…”
Section: Board Of Directors's Characteristicsmentioning
confidence: 99%
“…Clarkson et al (2003) showed that international audit firms present conservative audit behaviour to protect their reputation capital and to avoid risk of litigation. Conservatism can be clearly stated in the voluntary disclosure of intangible capital, because of the vague and contradicting regulations in this area (Vergauwen & Van Alem, 2005).…”
Section: C) the Auditor's Conservatismmentioning
confidence: 99%
“…However, their study did not make any attempt to provide empirically investigate the link between IT intensity and IT governance performance. This study examines the influence of IT intensity based on an approach similar to that used by Clarkson et al (2003).…”
Section: Corporate Communication Systemsmentioning
confidence: 99%